Quality assurance in radiation therapy study aid учебно-методическое пособие - Sukhikh specialist in the field of nuclear energy Associate Professor of Tomsk Polytechnic University, Candidate of Physical and Mathematical Sciences; Sagov nuclear technology specialist engineer of Tomsk Polytechnic University; Selikhova specialist in the field of nuclear technologies engineer of Tomsk Polytechnic University; Stakhova specialist in the field of nuclear technologies engineer of Tomsk Polytechnic University (TPU Publishing House, 2025)
This manual detail key points of the quality assurance in the radiation therapy department. It specifies the education, duties and requirements of radiation therapy staff, the basic physical procedures in qualified radiation therapy and steps in patient management: from patient registration to treatment. The practical part of this manual will delve more deeply into the routine work of the radiation therapy department. The book is intended for students studying in the directions 14.03.02, 14.04.02 "Nuclear physics and technologies", 31.08.61 "Radiotherapy", medical physicists, radiotherapists and radiotherapy technologists